(3GdcdGe GdebfY aj eSCdI GdeSeYs - (3GdeNJGQ Hf GdgjHI GdGfJTGFj,J (B1285 (3g` s
(3ChdgG (B:s
(3MeOkG def LYd ENJdGa GdYdeGA GdCFeI QMeg efg JYGdi dCeI fHi GdQMeI gPG hEf eSCdI GdeSeY JeS GdMGLI ajgG Edi cdGe ebfY hGdcdGe Ydi gPg GdeSCdI ai KdGKI CehQ s
(3BNQgG (B:s
(3hEfeG cGf EHdjS YOhkG dfG dgPG , hcGfJ GdCfHjGA Ydjge GdUdGI ChdjGA GdeDefjf ddSYi ai eUGdM BNQJge GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs